Peran Kepemimpinan dan Kompensasi dalam Meningkatkan Kepuasan Kerja Dosen: Analisis Kausalitas - Mawardi, Syamsi; Mukrodi, Mukrodi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Job satisfaction among lecturers is a crucial factor in improving the quality of higher education. Various studies indicate that leadership and compensation play significant roles in shaping lecturers' job satisfaction. However, challenges remain in ensuring these aspects function optimally within academic institutions. This study aims to analyze the influence of leadership and compensation on lecturers' job satisfaction. The research employs a quantitative method using multiple linear regression analysis. Data were collected through a survey of lecturers at a university and analyzed to examine the relationship between leadership, compensation, and job satisfaction. The results show that leadership and compensation have a positive and significant influence on lecturers' job satisfaction, with a determination value of 0.755. This finding indicates that these two factors contribute substantially to shaping job satisfaction among lecturers. These findings highlight the need for higher education institutions to enhance leadership quality and implement a fair and competitive compensation system to create a more productive work environment. Therefore, this study provides insights for university administrators in designing strategic policies to improve lecturers' satisfaction and performance.